2014
DOI: 10.1186/2193-1801-3-595
|View full text |Cite
|
Sign up to set email alerts
|

Selective internal radiation therapy of hepatic tumors: procedural implications of a patent hepatic falciform artery

Abstract: Selective internal radiation therapy (SIRT) using 90-yttrium is a local therapy for unresectable liver malignancies. Non-targeted 90-yttrium diversion via a patent hepatic falciform artery (HFA) is seen as risk for periprocedural complications. Therefore, this study aimed to evaluate the impact of a patent HFA on SIRT. 606 patients with SIRT between 2006 and 2012 were evaluated retrospectively. SIRT preparation was performed by digital subtraction angiography including 99mTc-HSAM administration and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 21 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…One of the first pioneers in performing radioembolization with 90 Y microspheres for colorectal cancer (CRC) hepatic metastases was Ariel, 2 a surgeon from New York, in animal experiments and subsequently in two human volunteers. Nolan and Grady 3 then described the use of 90 Y oxide to treat hepatocellular carcinoma (HCC) in humans. Subsequent clinical trials involved several successful treatments of metastatic CRC to the liver.…”
Section: Historical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the first pioneers in performing radioembolization with 90 Y microspheres for colorectal cancer (CRC) hepatic metastases was Ariel, 2 a surgeon from New York, in animal experiments and subsequently in two human volunteers. Nolan and Grady 3 then described the use of 90 Y oxide to treat hepatocellular carcinoma (HCC) in humans. Subsequent clinical trials involved several successful treatments of metastatic CRC to the liver.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…9 Metastatic liver tumours .3 mm derive 80-100% of their blood supply from arterial rather than portal hepatic circulation. 10 These concepts are the basis for intra-arterial administration of 90 Y microspheres. Two parts are present in this radioembolization procedure: embolization and brachytherapy.…”
Section: Radioembolization Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the falciform artery often originates far in the periphery of the hepatic artery, selective occlusion is often not possible. Schelhorn et al examined 19 SIRT patients with an open falciform artery [15]. It was able to be shown that a large-caliber, open falciform artery is not a contraindication for SIRT.…”
mentioning
confidence: 99%